2003
DOI: 10.1152/jn.00419.2003
|View full text |Cite
|
Sign up to set email alerts
|

Protracted Development of Responses to Whisker Deflection in Rat Trigeminal Ganglion Neurons

Abstract: Shoykhet, Michael, Pranav Shetty, Brandon S. Minnery, and Daniel J. Simons. Protracted development of responses to whisker deflection in rat trigeminal ganglion neurons. J Neurophysiol 90: 1432-1437. First published June 11, 2003 10.1152/jn.00419.2003. The rodent whisker-to-barrel pathway constitutes a major model system for studying experience-dependent brain development. Yet little is known about responses of neurons to whisker stimulation in young animals. Response properties of trigeminal ganglion (NV) neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 25 publications
(39 reference statements)
1
23
0
Order By: Relevance
“…In the PrV, barrelette cells receive inputs from whisker-specific trigeminal ganglion cells, which show either lowfrequency spontaneous or high-frequency sensory activities (Minnery and Simon, 2003;Shoykhet et al, 2003). If silent synapses are a consequence of the absence of high-frequency sensory inputs, then highfrequency electrical stimulation of the afferent pathway could convert silent synapses into functional synapses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the PrV, barrelette cells receive inputs from whisker-specific trigeminal ganglion cells, which show either lowfrequency spontaneous or high-frequency sensory activities (Minnery and Simon, 2003;Shoykhet et al, 2003). If silent synapses are a consequence of the absence of high-frequency sensory inputs, then highfrequency electrical stimulation of the afferent pathway could convert silent synapses into functional synapses.…”
Section: Resultsmentioning
confidence: 99%
“…More recent studies uncovered that trigeminal ganglion cells have TTXresistant Na ϩ and voltage-dependent Ca 2ϩ channels that produce Ca 2ϩ spikes (Kim and Chung, 1999;Cabanes et al, 2002). Furthermore, TTX or bupivacaine does not appear to block spontaneous activity of trigeminal ganglion cells Shoykhet et al, 2003). In contrast to pharmacological activity blockade experiments, gene deletion or alteration studies in mice showed that disruption of NMDA receptor subunits NR1 or NR2B prevent development of barrelette patterns altogether (Li et al, 1994;Kutsuwada et al, 1996;Iwasato et al, 1997).…”
Section: Physiological Evidence For Activity-dependent Plasticity In mentioning
confidence: 99%
“…In the barrel cortex of rodents, neurons are selective for the angular direction in which their corresponding mystacial whisker [the principal whisker (PW)] is deflected (Simons, 1983;Simons and Carvell, 1989;Bruno and Simons, 2002). Direction selectivity is already present in the principal trigeminal nucleus Shoykhet et al, 2003) and in the ventrobasal nucleus of the thalamus (Simons and Carvell, 1989;Bruno et al, 2003;Timofeeva et al, 2003). Therefore, the spike output tuning of individual barrel cortex cells may simply be a faithful reproduction of the tuning properties of their synaptic inputs, or, alternatively, postsynaptic mechanisms may transform a broadly tuned synaptic input into a sharply tuned spike output.…”
Section: Introductionmentioning
confidence: 99%
“…Responses of rapidly adapting cutaneous receptors are moderately affected by tissue viscoelasticity (Grigg et al 2004). In the vibrissa system, trigeminal ganglion neurons fire progressively more robustly during the first postnatal month, presumably reflecting changes in the mechanical properties of the facial tissue (Shoykhet et al 2003), and in adult animals paralyzed by neuromuscular blockade the lack of facial muscle tone often leads to the failure of a deflected whisker to return autonomously to its neutral position following whisker displacement (Minnery and Simons 2003). Here we examine further possible effects of tissue compliance by comparing responses of trigeminal ganglion neurons recorded separately during experiments in which animals were or were not subject to neuromuscular blockade.…”
mentioning
confidence: 99%